2006
DOI: 10.1111/j.1365-2125.2006.02793.x
|View full text |Cite
|
Sign up to set email alerts
|

Possible interethnic differences in quinidine‐induced QT prolongation between healthy Caucasian and Korean subjects

Abstract: AimsThe aim of this study was to evaluate the pharmacokinetics and pharmacodynamics of quinidine-induced QT prolongation in healthy Caucasian and Korean subjects to investigate interethnic differences in susceptibility to drug-induced arrhythmia. MethodsA randomized, double-blind crossover study was conducted in 24 (12 male and 12 female) Korean and 13 (seven male and six female) Caucasian subjects. After a 20 min infusion of quinidine (4 mg kg -1 ) or saline, the serum concentration of quinidine and the QT in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
47
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(53 citation statements)
references
References 34 publications
5
47
1
Order By: Relevance
“…Our data and other studies with potent QT prolonging drugs [27,31] suggest that women can be more sensitive to delay in cardiac repolarization induced by some drugs, as previously suggested by Woolsey's group [27], supported by in vitro experiments with quinidine [32] and with erythromycin [18]. Such a gender-based difference in sensitivity can be caused by hormonal effects, or differences in regard to the expression or activity of ion channels that regulate repolarization in the cardiomyocyte.…”
Section: Figuresupporting
confidence: 83%
“…Our data and other studies with potent QT prolonging drugs [27,31] suggest that women can be more sensitive to delay in cardiac repolarization induced by some drugs, as previously suggested by Woolsey's group [27], supported by in vitro experiments with quinidine [32] and with erythromycin [18]. Such a gender-based difference in sensitivity can be caused by hormonal effects, or differences in regard to the expression or activity of ion channels that regulate repolarization in the cardiomyocyte.…”
Section: Figuresupporting
confidence: 83%
“…It is reported that quinidine concentrations in white British subjects tended to be lower than those in Nigerians, yet the quinidine-induced QTc increase was greater in white British subjects than in Nigerians (Olatunde and Price Evans 1982). Also, it is suggested that Korean subjects are less sensitive to quinidine-induced QTc prolongation than Caucasian subjects (Shin et al 2006). On the other hand, it is reported that, among normotensives, compared with whites, QTc is shorter in African-American and longer in Chinese, indicating that QTc parameter showed variation between different ethnic groups (Chapman et al 2000).…”
Section: Resultsmentioning
confidence: 95%
“…These determinants might lead to differences in the basic pattern and/or drug-induced QTc changes. There are relatively few data on interethnic differences in druginduced QT prolongation (Olatunde and Price Evans 1982;Shin et al 2006). It is reported that quinidine concentrations in white British subjects tended to be lower than those in Nigerians, yet the quinidine-induced QTc increase was greater in white British subjects than in Nigerians (Olatunde and Price Evans 1982).…”
Section: Resultsmentioning
confidence: 96%
“…It is also well documented that women are at higher risk for the development of proarrhythmias caused by drugs with an effect on cardiac repolarization, i.e., drugs that prolong the QTc interval (Bednar et al 2002;Ebert et al 2000;Makkar et al 1993). It would therefore seem reasonable to assume that women also react with a larger degree of QTc prolongation than men at the same plasma exposure of a drug, and there are a few documented examples thereof (Rodriguez et al 2001;Benton et al 2000;Shin et al 2007;). For drugs with only a mild effect on the QT interval, it has been difficult to demonstrate a gender difference in sensitivity for the drug-induced QTc prolongation.…”
Section: Study Populationmentioning
confidence: 90%